A Case of Life‐threatening Staphylococcus aureus Endocarditis Involving Percutaneous Transcatheter Prosthetic Pulmonary Valve. (24th October 2012) - Bhat, Deepti P.; Forbes, Thomas J.; Aggarwal, Sanjeev
Abstract While right ventricle to pulmonary artery homograft is the surgical procedure of choice for relieving right ventricle outflow tract obstruction; it is limited by the need for multiple surgical replacements owing to progressive conduit obstruction, valve dysfunction, or patient growth. Since January 2010, percutaneous transcatheter placement of prosthetic pulmonary valve (Melody valve) has emerged as an attractive alternative to surgical replacement of dysfunctional right ventricle to pulmonary artery homograft in the United States. We report a case of 19‐year‐old girl born with truncus arteriosus who underwent transcatheter placement of prosthetic pulmonary valve due to homograft insufficiency. She presented after 4 months with a febrile episode and was found to have Staphylococcus aureus endocarditis of her prosthetic valve. The infection caused multi‐organ dysfunction despite bacteriological clearance and led to severe dysfunction of the valve which ultimately required surgical removal. The case highlights a rare but serious complication of percutaneous prosthetic pulmonary valves.